221k views
0 votes
Y=X^2+4.6x+4.7 and y=3.3x-3.7

User Axolotl
by
5.2k points

2 Answers

4 votes

Answer:

Substitute one y for the other:

x^2 + 4.6x + 4.7 = 3.3x - 3.7

------

x^2 + 1.3x + 8.4 = 0

-----

x = [-1.3 +- sqrt(1.69-4*8.4)]/2

---

x = [-1.3 +-sqrt(-31.91)]/2

----

That gives 2 complex number solution for "y".

Explanation:

User Franck Valentin
by
5.0k points
1 vote

Answer:

Substitute one y for the other:

x^2 + 4.6x + 4.7 = 3.3x - 3.7

------

x^2 + 1.3x + 8.4 = 0

-----

x = [-1.3 +- sqrt(1.69-4*8.4)]/2

---

x = [-1.3 +-sqrt(-31.91)]/2

----

That gives 2 complex number solution for "y".

That looks rather strange. Did you post the

problem correctly?

Cheers,

User Jxtps
by
4.5k points